Phylogeny of Asian Bufonids inferred from mitochondrial DNA sequences (Anura: Amphibia): implication for the speciation of East Asian Bufonids. (4th May 2017) - Peng, Zhaojie; Pan, Tao; Wan, Yaqiong; Qian, Lifu; Wu, Jun; Zhang, Baowei
Abstract: Many bufonidae species distributed in Asia are inhabited in a variety of environments. However, there are few studies focusing on the speciation of Asia Bufonidae. In this study, we reconstruct the phylogeny tree of Asia Bufonidae with timescale in BEAST based on a multiple sequence alignment of 12S gene and 16S gene sequences from 13 Bufonidae species and whole mtDNA from five Bufonidae species. The results show that the bufonids split into two major clades. In general, there are two lineages mainly distributed on different sides of the Himalayas. According to the divergence time and distribution of the two lineages, we imply that the differentiation of Bufonidea may be closely linked to the uplift of QTP and consequent monsoon climate.